'Blazing the trail or exposing the gaps?' Discourses on student-centredness in genre independent and classical music performance study programmes in Norway and the Netherlands. (1st January 2022) - Ski-Berg, Veronica
ABSTRACT: Student-centredness is being advocated for in research on higher music education (HME), yet its perils have been largely neglected by scholars. While issues of employability are important to address in order for music graduates to thrive in a neoliberal world, this article asserts that the underlying power mechanisms that are being criticised for stifling creative development in students may continue to exist also within student-centred environments. By turning to a discourse-theoretical Foucauldian framework, the article presents empirical data from a comparative case study of two HME institutions. The findings suggest that there are four discourses (of employability, artistry, craftsmanship, and holism ) on student-centredness in HME. Moreover, tension points between students, professors, study programmes, and discourses may be softened if student-centredness is allowed more nuances. Finally, the article discusses how the subject positions of music performance students and professors are transformed by student-centredness, and how this transformation is affecting HME institutions.